A model for surgical volunteerism: a qualitative study based in Cambodia. (January 2020) - Cheok, Sabrina; Dong, Chaoyan; Lam, Wee Leon; Gollogly, Jim; Rajaratnam, Vaikunthan
Medical volunteerism continues to attract many doctors from high-income nations to low- or middle-income countries (LMIC). In spite of the wealth of positive experiences of these volunteers documented in the literature, there is little evidence concerning the impact and effectiveness of their activity. We documented our model of five-year experience in the delivery of hand surgery in Cambodia, attempting a qualitative approach with attempts to understand the perceptions of local and volunteer surgeons. We conducted independent qualitative interviews with five visiting and 12 Cambodian surgeons who participated in our community-based and outcome-oriented hand surgery training programme between 2013 and 2015. Data were coded and analysed using a content analysis method and then individually grouped into categories; software was used to generate frequencies and quotations of codes. Our results highlighted factors contributing to the success of the medical volunteering programme, to its success, with suggestions for sustainability, motivation and commitment to such a programme. A clearly defined strategy by the volunteer group and a commitment to time and resources by both partners were found to be effective.